1994
DOI: 10.1002/abio.370140312
|View full text |Cite
|
Sign up to set email alerts
|

Granulation of digested sewage sludge in mesophilic UASB reactors treating distillery waste waters from sugar cane molasses

Abstract: Five 4.02-1 UASB (Upflow Anaerobic Sludge Blanket) reactors were continuously operated at 30 "C under different hydrodynamic regimes for more than 120 days. The effect of the upflow liquid velocity (ULV) over the range of 0.25 to 2.0 m/h on the biological characteristics of the granules formed by treating vinasses (waste water of alcohol distilleries) from sugar cane molasses was investigated constantly maintaining the volumetric loading rate (VLR) (8 g COD1 . d). Granular sludge was found at all the ULV teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1997
1997
2002
2002

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…This phenomenon has been experimentally verified in aerobic biofilms: fast growing heterotrophic organisms are located at the outside, whereas slower growing nitrifying organisms can be found at the inside (Okabe et al, 1995;Okabe et al, 1996;Tijhuis et al, 1996;Watanabe et al, 1990). A similar structural organization has been observed in anaerobic, methanogenic granules and sulfate reducing granules as well (MacLeod et al, 1990;Ramos et al, 1994;van Houten et al, 1995).…”
Section: Introductionsupporting
confidence: 55%
“…This phenomenon has been experimentally verified in aerobic biofilms: fast growing heterotrophic organisms are located at the outside, whereas slower growing nitrifying organisms can be found at the inside (Okabe et al, 1995;Okabe et al, 1996;Tijhuis et al, 1996;Watanabe et al, 1990). A similar structural organization has been observed in anaerobic, methanogenic granules and sulfate reducing granules as well (MacLeod et al, 1990;Ramos et al, 1994;van Houten et al, 1995).…”
Section: Introductionsupporting
confidence: 55%
“…During the treatment of effluents composed mainly of carbohydrates in the mesophilic range of temperatures (35ºC), the granulation process appears to develop slowly as the influent COD concentration decreases to below 500 mg COD/l (Ramos et al, 1994). Other researchers reported that granulation did not occur during the startup of UASB digesters treating a synthetic wastewater composed mainly of glucose (Brito et al, 1997), or during the treatment of a glucose-supplemented domestic sewage (Gnanadiphathy and Polprasert, 1993).…”
Section: Discussionmentioning
confidence: 99%